Advantages of a variable‐resolution global climate model in reproducing the seasonal evolution of East Asian summer monsoon. (22nd July 2022) - Zhu, Haonan; Zhang, Jie; Xu, Zexuan; Di Vittorio, Alan V.; Xin, Xiaoge; Xiao, Chan; Li, Yonghua
Abstract: The East Asian summer monsoon (EASM) is unique among monsoon systems that it features meridional evolution of the summer monsoon. In this study, we evaluate the performances of a Variable‐Resolution Community Earth System Model (VR‐CESM) regionally refined over eastern China (14 km) in reproducing the seasonal evolution of EASM precipitation over China. Compared with reference datasets, VR‐CESM shows better performance than the corresponding globally uniform coarse‐resolution model CESM (quasi‐uniform 1°), especially over western China where complex local topography exists. The northward monsoon migration is closely related to low‐level southerly flows and vertical moisture advection, which are more reasonably simulated in VR‐CESM. The four critical timings of the EASM (monsoon onset, withdrawal, peak, and duration) are also better captured in VR‐CESM than in CESM. The corresponding spatial Pearson correlation coefficients of the four critical timings with respect to reference datasets are about 0.1 higher in VR‐CESM than those in CESM. Both models are most accurate in simulating monsoon onset and least accurate at simulating the monsoon peak. The overestimated zonal thermal contrast in CESM is responsible for the earlier monsoon onset and excessive precipitation in September over the Yangtze River valley. Finer resolution in VR‐CESM, especially over the Tibetan Plateau (TP), appears to be a main factor in simulating better zonal thermal contrast and seasonal evolution of the EASM. Abstract : The four critical timings of EASM (monsoon onset, withdrawal, peak, and duration) are better captured in VR‐CESM. The corresponding spatial correlation coefficients of the four timings with respect to reference datasets are about 0.1 higher in VR‐CESM than those in CESM.